Salivary Fluoride Levels after Use of High-Fluoride Dentifrice - Glauber Campos Vale; Priscila Figueiredo Cruz; Ana Clarissa Cavalcante Elvas Bohn; Marcoeli Silva de Moura (The Scientific World Journal)
The aim of the study was to evaluate salivary fluoride (F) availability after toothbrushing with a high-F dentifrice. Twelve adult volunteers took part in this crossover and blind study. F concentration in saliva was determined after brushing with a high-F dentifrice (5000 µg F/g) or with a conventional F concentration dentifrice (1100 µg F/g) followed by a 15 mL distilled water rinse. Samples of nonstimulated saliva were collected on the following times: before (baseline), and immediately after spit (time = 0) and after 1, 2, 3, 4, 5, 10, 15, 20, 30, 45, 60, 90, and 120 min. F analysis was performed with a fluoride-sensitive electrode and the area under curve of F salivary concentration × time (µg F/mL × min−1) was calculated. At baseline, no significant difference was found among dentifrices (P > 0.05). After brushing, both dentifrices caused an elevated fluoride level in saliva; however salivary F concentration was significantly higher at all times, when high-F dentifrice was used (P < 0.01). Even after 120 min, salivary F concentration was still higher than the baseline values for both dentifrices (P < 0.001). High-F dentifrice enhanced the bioavailability of salivary F, being an option for caries management in patients with high caries risk.